2023
DOI: 10.3390/genes14030635
|View full text |Cite
|
Sign up to set email alerts
|

Familial 4p Interstitial Deletion Provides New Insights and Candidate Genes Underlying This Rare Condition

Abstract: Chromosome 4p deletions can lead to two distinct phenotypic outcomes: Wolf-–Hirschhorn syndrome (a terminal deletion at 4p16.3) and less frequently reported proximal interstitial deletions (4p11-p16). Proximal 4p interstitial deletions can result in mild to moderate intellectual disability, facial dysmorphisms, and a tall thin body habitus. To date, only 35 cases of proximal 4p interstitial deletions have been reported, and only two of these cases have been familial. The critical region for this syndrome has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…There are no more than 40 cases reporting interstitial deletions or duplications on the proximal short arm of chromosome 4 and few involving alterations in STIM2 alleles. The most prevalent phenotype associated with such chromosomal alterations is intellectual disability, presenting other clinical features to a minor degree, such as physical and facial dimorphism or congenital heart diseases [ 87 , 88 ]. For instance, two studies involving STIM2 allele duplication were reported.…”
Section: Stim2 In Human Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no more than 40 cases reporting interstitial deletions or duplications on the proximal short arm of chromosome 4 and few involving alterations in STIM2 alleles. The most prevalent phenotype associated with such chromosomal alterations is intellectual disability, presenting other clinical features to a minor degree, such as physical and facial dimorphism or congenital heart diseases [ 87 , 88 ]. For instance, two studies involving STIM2 allele duplication were reported.…”
Section: Stim2 In Human Diseasesmentioning
confidence: 99%
“…The first study performed genetic analyses on a 3-year-old proband displaying physical and intellectual delay, microcephaly, diverse facial anomalies, anxiety, frequent laughing, and hypermobility of the elbows. A deletion of a region of 3.4 Mb in size was found at 4p15.2-p14, generating haploinsufficiency in STIM2 and 15 additional genes [ 87 ]. From those 16 genes, the authors restricted to five (DHX15, PCDH7, PPARGC1A, RBPJ, and STIM2) the major contributors to the phenotype.…”
Section: Stim2 In Human Diseasesmentioning
confidence: 99%